Angiotensin-converting enzyme inhibitors and motor neuron disease: An unconfirmed association. Issue 5 (17th August 2016) - Franchi, Carlotta; Bianchi, Elisa; Pupillo, Elisabetta; Poloni, Marco; Nobili, Alessandro; Fortino, Ida; Bortolotti, Angela; Merlino, Luca; Beghi, Ettore
Abstract: Objective : To investigate the association between angiotensin converting enzyme inhibitors (ACEIs), angiotensin II receptors blockers (ARBs) and motor neuron disease (MND). Methods : This is a population-based nested case-control study. Data were obtained from a population registry and the administrative database of the Lombardy Region (Northern Italy) from 2000 through 2010. Included were 1, 200 patients with newly diagnosed MND/ALS and 120, 000 controls, randomly selected from the same population and matched for gender, age and area of residence. Exposure to ACEIs or ARBs was quantified using defined daily doses (DDDs). Cumulative DDD (cDDD) was estimated as the sum of dispensed DDDs in the preceding 5 years, excluding 1 year before the MND/ALS diagnosis. Overall exposure, levels of exposure, and individual drugs were all assessed. Subgroup analyses were performed according to age, sex, ALS and ACEI-ARB association. Results : There was no significant association between MND/ALS and antecedent use of ACEIs or ARBs. Data were confirmed in multivariable models and in subgroups. Conclusions : A protective role of ACEIs and ARBs in MND was not confirmed. Differences with a previous report (showing an inverse association between ACEIs and ALS) can be explained by different genetic background, dietary habits and susceptibility to environmental exposures, including drugs.